2011
DOI: 10.1128/jcm.02157-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Xpert MTB/RIF Test with an IS 6110 -TaqMan Real-Time PCR Assay for Direct Detection of Mycobacterium tuberculosis in Respiratory and Nonrespiratory Specimens

Abstract: The sensitivities of the Xpert MTB/RIF test and an in-house IS6110-based real-time PCR using TaqMan probes (IS6110-TaqMan assay) for the detection of Mycobacterium tuberculosis complex (MTBC) DNA were compared by use of 117 clinical specimens (97 culture positive and 20 culture negative for MTBC) that were frozen in sediment. The 97 clinical specimens included 60 respiratory and 37 nonrespiratory specimens distributed into 36 smear-positive and 61 smear-negative specimens. Among the 97 culture-positive specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
124
8
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 20 publications
16
124
8
9
Order By: Relevance
“…Culture of bronchoscopy sample for MTB was not done because of time factor, cumbersome, and cost effectiveness. Similar yields were documented in studies by Pierrae et al [31] as 80%, Bernard et al [32] as 92.3%, Khalil et al [33] as 91.86%, Lee et al [34] as 81.6%, and Surendra et al [35] as 90%, and few other studies [36][37][38][39] from various authors documented sensitivity between 57% and 75%.…”
Section: Diagnostic Yield Of Bronchoscopy Guided Techniques In Llf Tbsupporting
confidence: 68%
“…Culture of bronchoscopy sample for MTB was not done because of time factor, cumbersome, and cost effectiveness. Similar yields were documented in studies by Pierrae et al [31] as 80%, Bernard et al [32] as 92.3%, Khalil et al [33] as 91.86%, Lee et al [34] as 81.6%, and Surendra et al [35] as 90%, and few other studies [36][37][38][39] from various authors documented sensitivity between 57% and 75%.…”
Section: Diagnostic Yield Of Bronchoscopy Guided Techniques In Llf Tbsupporting
confidence: 68%
“…The sensitivity of real-time PCR and X-pert MTB/RIF are given similar results with smears positive, but it is low in real-time technique for smears negative. These are matching with Armand et al, 18 who suggested that both methods were highly specific and exhibited excellent sensitivity (100%) with smear-positive specimens, but does not match in the sensitivity of the X-pert MTB/RIF test with the smear-negative specimens were more reduced than that of the real-time PCR assay (48 versus 69%, P < 0.005).…”
Section: Discussionsupporting
confidence: 73%
“…There is a large number of studies evaluating Xpert on pulmonary specimens [5,6,[17][18][19][20][21][22][23]; the sensitivity varies from 95% to 100% in smear-positive sputa, and from 47% to 77% in smear-negative ones. Our data score high within these ranges, despite the well-known lower yield of extrapulmonary samples in term of sensitivity.…”
Section: Discussionmentioning
confidence: 99%